The Moderating Role of Work Environment in the Relationship Between Organisational Culture, Employee Motivation, Performance Appraisal, and Job Satisfaction in Bali's Hotel Industry - Ginting, Yanti Mayasari; Rismawati, Rismawati; Aisyah, Siti (UI Scholars Hub, 2024)
Research Aims: This study examines the effects of organisational culture, employee motivation, performance appraisal, and the work environment as a moderator on job satisfaction in Bali's hotel industry, addressing gaps in HRM literature. Design/Methodology/Approach: Data were collected via structured questionnaires from 305 hotel employees in Bali. SmartPLS software analysis included model evaluation, validity testing, and path coefficient and moderator analyses. Research Findings: Organisational culture, employee motivation, and performance appraisal significantly influence job satisfaction. The work environment moderates these relationships, enhancing the positive effects of HRM practices. Theoretical Contribution/Originality: This study highlights the work environment’s pivotal role in strengthening HRM practices' impact on job satisfaction. It offers insights for hotel managers and HR professionals to enhance employee satisfaction and organisational performance. Managerial Implication in the South East Asian Context: Fostering a positive work environment is critical in Southeast Asia. Managers should create collaborative and well-resourced workplaces to align organisational culture, motivation, and performance appraisal with employee satisfaction. Research Limitation & Implications: Self-reported data may introduce response bias, limiting the study’s scope to hotel employees in Bali. Future research should explore diverse contexts for broader applicability.